2020
DOI: 10.1080/15599612.2020.1828516
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy logic based feedback control system for the frequency stabilization of external-cavity semiconductor lasers

Abstract: This paper proposes an intelligent approach (fuzzy logic) for the design of external-cavity semiconductor lasers (ECLs) for better disturbance rejection. As a kind of nonlinear optical system, ECL output frequency is difficult to be stabilized by conventional methods. The fuzzy logic algorithm is preferred for ECLs stabilization, which could update parameters automatically. Suddenability to reject nonlinear disturbances arch occur in the fuzzy logic systemduring operation, speed of operation and PID gains are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Martin et al 24 showed the laser frequency stabilization of an ECDL onto a line in the tellurium spectrum via saturation spectroscopy, and increased the duration of stable single‐frequency operation from hours to days by stabilizing the laser to a tellurium absorption line at 452.756 nm. Recently, the fuzzy logic algorithm 25 for ECLs stabilization was developed with higher performances.…”
Section: Figurementioning
confidence: 99%
“…Martin et al 24 showed the laser frequency stabilization of an ECDL onto a line in the tellurium spectrum via saturation spectroscopy, and increased the duration of stable single‐frequency operation from hours to days by stabilizing the laser to a tellurium absorption line at 452.756 nm. Recently, the fuzzy logic algorithm 25 for ECLs stabilization was developed with higher performances.…”
Section: Figurementioning
confidence: 99%
“…The second direction is to design all-optical logic devices [1][2][3][4][5][6] on the physical principles of interference, polarization, and coherence, as well as the use of the properties of diffraction gratings and photonic crystals. The researchers demonstrated experimental results [7,8] that showed an increase in the performance of all-optical devices. The wider use of such devices is hampered by currently imperfect production technologies.…”
Section: Introductionmentioning
confidence: 97%
“…Due to these practical successes, fuzzy data processing has become an important part of data processing in general. So, not surprisingly, researchers have shown interest in the use of optical computing for processing fuzzy data [16][17][18][19][20][21][22][23][24][25][26][27]. The first optical computing devices for processing fuzzy data were based on several different ideas: on the representation of logical operations using the optical effect of anisotropic scattering [16], on a programmable array of prisms [17], and on the calibration of shadow diagrams, for example, an optical system based on a zone coding scheme and a shadow casting method [18].…”
mentioning
confidence: 99%
“…Systems in which optical computing is used for processing fuzzy data have been successfully used in technical applications; see, e.g., [25,26]. However, such systems…”
mentioning
confidence: 99%